Nigel R. Badnell (1958–2024): A Legacy in Atomic Astrophysics - Giulio Del Zanna; Helen E. Mason; Peter J. Storey; Stefan Kuhr; Chunyu Zhang; Junjie Mao; Gary J. Ferland; Alessandra Giunta; Roger P. Dufresne (Atoms, 2025)
Nigel Robert Badnell was born on the 27th of October 1958 and grew up in Swindon where he lived with his parents, Dave and Patricia, and his wee sister, Hilary [...]